Seven cancer patients receiving Guselkumab for treatment of moderate-to-severe psoriasis - Luca Mastorino; Niccolò Siliquini; Gianluca Avallone; Michela Ortoncelli; Pietro Quaglino; Paolo Dapavo; Simone Ribero (PAGEPress Publications, 2022)
not available